Graphs and Their Applications in Various Fields - N.S. Kurbonova (Genius Journals, 2022)
The article provides information on the theory of graphs, types of graphs and the application of graphs to various fields. A number of problems have been solved using graphs as examples. The article also contains a number of recommendations for math teachers on the use of graphs.
Keywords: Graph Theory; Graph; Graph Tip; Graph Edge